The human capital endowment of Latin America and the Caribbean (2005)
Seeks to clarify the concept of human capital, with special reference to the ways in which it can be acquired. Provides an international indicator that takes account of all the shades of meaning of the definition proposed. Deals with issues such as health, formal and informal education and experience. Makes a diagnosis of the situation in Latin America and the Caribbean.
Bibliography: p. 115-116